Effect Of Tax Expense, Tunneling Incentive, Mechanism Bonus on Transfer Pricing Decisions - Varucha Ridha Lubis; Nur Afni Yunita; Nurhasanah (LPPM Universitas Malikussaleh, 2022)
This study aims to examine the effect of the Tax expense, Tunneling Incentive, Bonus Mechanism on Transfer Pricing decisions. The sample in this study are manufacturing companies in the Consumer Cyclicals sector in 2019-2021. The sampling technique used was purposive sampling in order to obtain a sample of 57 companies that met certain criteria for 3 consecutive years, from 2019-2021. The data used is secondary data sourced from the company's annual financial reports through the website www.idx.co.id. The results of the study show that the Tax expense has no significant effect on transfer pricing. While the Tunneling Incentive has a significant effect on Transfer Pricing, the bonus mechanism has no significant effect on Transfer Pricing. The coefficient of determination in this study shows a value of 0.064488. meaning that the independent variable has an influence of 0.06% while the remaining 99.4% is influenced by other variables not included in the model.